Istiqomah Sholat Subuh sebagai Indikator Implementasi Nilai Taqwa dalam Kurikulum Penjas PETIK pada Mahasiswa Semester III - Hariadi Said; Ikhlas Abdulah (Transbahasa, 2025)
This study examines the consistency of performing the Fajr prayer among third-semester students of the Physical Education Study Program, Faculty of Sports and Health, Universitas Negeri Gorontalo, as an indicator of the implementation of piety (taqwa) values in the PETIK Physical Education curriculum (Professional, Empathy, Piety, Innovative, Creative). The study also analyzes the relationship between Fajr prayer habituation and students’ readiness to participate in lectures with a calmer and more focused mental state. This research supports the Diktisaintek Berdampak program, which emphasizes character strengthening through daily religious practices in higher education. A quantitative approach with a one-group quasi-experimental design was employed. The participants consisted of 98 third-semester students whose Fajr prayer practices were monitored over one semester (16 weeks) with an ideal frequency of 112 prayers. Monitoring was conducted through a WhatsApp group, where students reported the performance of the Fajr prayer within the time range of 04:10–05:45 WITA. Data were analyzed descriptively by calculating the total number of on-time Fajr prayers and classifying them into five levels of consistency. The results showed that 9.18% of students were categorized as very consistent, 38.78% consistent, 21.43% moderately consistent, 20.41% less consistent, and 10.20% very less consistent. Overall, 69.39% of students demonstrated a moderate to very high level of Fajr prayer consistency. These findings indicate that structured habituation of the Fajr prayer contributes positively to the implementation of piety values in the PETIK curriculum and supports the development of disciplined and well-prepared students.